Medicago sativa L. subsp. sativa APG 6913 ... - GLIS Of The ITPGRFA (Australian Pastures Genebank of the South Australian Research and Development Institute, 2023)
Plant Genetic Resource. Taxonomy: Medicago sativa L. subsp. sativa Common name(s): Lucerne Other names: ORCA Conserved by: Australian Pastures Genebank of the South Australian Research and Development Institute (APG), Australia Local sample unique identifier: APG 6913 Method of creation: Acquisition Date: 1971-12-01 Other identifiers: n/a,SA 6913, n/a,I 726, n/a,CPI 53247, n/a,413, n/a,ORCA, n/a,ALP 1.3 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...